Nitrogen Metabolism and Growth Enhancement in Tomato Plants Challenged with Trichoderma harzianum Expressing the Aspergillus nidulans Acetamidase amdS Gene - Domínguez, Sara; Rubio, M. Belén; Cardoza, Rosa E.; Gutiérrez, Santiago; Nicolás, Carlos; Bettiol, Wagner; Hermosa, Rosa; Monte, Enrique (Frontiers in Microbiology, 2016)
Trichoderma is a fungal genus that includes species that are currently being used as biological control agents and/or as biofertilizers. In addition to the direct application of Trichoderma spp. as biocontrol agents in plant protection, recent studies have focused on the beneficial responses exerted on plants, stimulating the growth, activating the defenses, and/or improving nutrient uptake. The amdS gene, encoding an acetamidase of Aspergillus, has been used as a selectable marker for the transformation of filamentous fungi, including Trichoderma spp., but the physiological effects of the introduction of this gene into the genome of these microorganisms still remains unexplored. No evidence of amdS orthologous genes has been detected within the Trichoderma spp. genomes and the amdS heterologous expression in T. harzianum T34 did not affect the growth of this fungus in media lacking acetamide. However, it did confer the ability for the fungus to use this amide as a nitrogen source. Although a similar antagonistic behavior was observed for T34 and amdS transformants in dual cultures against Rhizoctonia solani, Botrytis cinerea and Fusarium oxysporum, a significantly higher antifungal activity was detected in amdS transformants against F. oxysporum, compared to that of T34, in membrane assays on media lacking acetamide. In Trichoderma-tomato interaction assays, amdS transformants were able to promote plant growth to a greater extent than the wild-type T34, although compared with this strain the transformants showed similar capability to colonize tomato roots. Gene expression patterns from aerial parts of 3-week-old tomato plants treated with T34 and the amdS transformants have also been investigated using GeneChip Tomato Genome Arrays. The downregulation of defense genes and the upregulation of carbon and nitrogen metabolism genes observed in the microarrays were accompanied by i) enhanced growth, ii) increased carbon and nitrogen levels and iii) a higher sensitivity to Botrytis cinerea infections in plants treated with amdS transformants as detected in greenhouse assays. These observations suggest that the increased plant development promoted by the amdS transformants was at expense of defenses.